The historical relationship between African indigenous healing practices and Western-orientated biomedicine in South Africa: A challenge to collaboration - Guma, Phillip M. (HTS teologiese studies, 2020)
South African traditional medicine is based on centuries-old cultural heritage, yet it remains popular today, used by a significant percentage of the population. It has adapted to changing times, endured persecution by unfriendly governments and now enjoys a new status with the government’s adoption of the Traditional Health Practitioners Act 35 of 2004. The adoption of this act was an important first step by the national government towards the integration of traditional and Western health systems in official health services. However, many challenges still need to be addressed. Competition between traditional healers in Keiskammahoek has resulted in low participation in local traditional healers’ councils, posing a significant challenge to future cooperative efforts between traditional healers and biomedical practitioners. Although biomedical practitioners have expressed mixed views on collaboration with traditional healers, exposure to traditional healers on a professional level, together with an understanding of traditional medicine theory, helps to foster an understanding and willingness to work with traditional healers. This article discusses the ways in which political consciousness and social dialogues have strongly influenced the relationships between different healthcare systems in South Africa, as well as the continuing challenges of healthcare delivery in the Eastern Cape.Contribution: This article hopes to expand the long-debated call to integrate African indigenous medicine into the mainstream medical practice that continues to favour biomedicine to the detriment of local practices of medicine and healthcare.